Experimental-use Permits - Frederick M. Fishel (EDIS)
Experimental use of pesticides refers to formal research efforts conducted to scientifically assess the pest control potential of a registered pesticide or an experimental pesticide. This document is PI-56, one of a series of the Agronomy Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date August 2005.